13 Health status of adolescent girls employed in the textile industry of tamil nadu, india. (24th April 2018) - Joseph, B; Gnanaselvam, NA
Abstract : Introduction: A 'marriage assistance scheme' prevails in Tamil Nadu, India, where unmarried adolescent girls are recruited to work for specified periods of time in textile factories in return for a bulk amount of money at the end of tenure, which is used for their marriage expenses. We aimed to assess the health status of adolescent girls working in such factories. Methods: A total of 321 adolescent girls, 107 in each study group namely, current employees, past employees and the never-been employed were interviewed for the study. Standard tools used to evaluate the health and wellbeing of the adolescents. Result: Significant difference was observed among the study groups in terms of health practices such as physical activity, hours of sleep, consumption of fruits and vegetables, and access to health care. Prevalence of menstrual irregularities was more among the current employees and past employees with 38.3% and 37.4% of them affected as compared to 18.7% among the never-been employed girls [AOR 2.42 (95% CI: 1.42 to 4.72)]. Among the current and the past employees, 30% reported abuse at workplace. Significant difference in conditions such as depression and behavioural problems including emotional, conduct, hyperactivity and peer-relation problems were observed between the study groups, with more number of current and past employees suffering from these issues as compared to the never-been employed adolescents [AOR 2.25 (95% CI: 1.22 to 4.14)]. Musculoskeletal pain was also more among the current and past employees, with neck and shoulder being the common regions of the body which were affected [AOR 5.28 (95% CI: 2.13 to 13.1)]. Discussion: Current and past employees have poorer health as compared to the never-been employed adolescents. Workplace counselling could prevent mental health morbidities among the employed adolescent girls. Appropriate ergonomic measures must be undertaken at workplaces to avoid musculoskeletal disorders among current employee.